Modeling of non point source pollution from residental and commercial catchments in Skudai, Johor - Rahmat, Siti Nazahiyah (2005)
Sampling of urban runoff was carried out in two small catchments, which represent residential and commercial areas in Skudai, Johor. Ten storm events for residential and seven events for commercial catchments were analysed. Runoff quality showed large variations in concentrations during storms, especially for SS, BOD5 and COD. Concentrations of NO3-N, NO2-N, NH3-N, and P were also high. Lead (Pb) was also detected in both catchments but the levels were low (<0.001 mg/l). In general, the water quality was badly polluted and fell in class V of the Interim National Water Quality Standards. The hydrographs and pollutographs for both catchments showed rapid increases and decreases equally rapidly. Most pollutants were diluted as storm events progress. In most cases, the peak concentrations preceded the peak runoff. This suggests that the pollutants were of short distant sources/origins and the bulk of the pollutant mass arrived at the catchment’s outlet much faster than the runoff itself. For the hysteresis loop, both catchments showed most of the parameters were characterized by clockwise hysteresis. Only a few plots were exhibited counterclockwise and figure eight hysteresis loop. The relative strength of the first flush for the commercial catchment was P> COD>SS> NO3-N> NO2-N> BOD5> NH3-N whereas for the residential catchment was SS> COD> BOD5> NH3-N> P> NO3-N> NO2-N. The loadings were higher in the commercial than in the residential catchment and this was attributed to a greater runoff volume per unit area and higher Event Mean Concentration (EMC) in the former. Detail calibration and validation of Storm Water Management Model (SWMM) for modeling water quantity and quality were discussed. The simulation results, evaluated in terms of runoff depth, peak flow and the hydrograph shapes, were satisfactorily. For the water quality modeling, the simulation results were evaluated in terms of total load and peak load. SWMM can model SS load reasonably well for the residential catchment, but was not satisfactory for the commercial catchment.